2017
DOI: 10.1145/3059005
|View full text |Cite
|
Sign up to set email alerts
|

Affective Calibration of Musical Feature Sets in an Emotionally Intelligent Music Composition System

Abstract: Affectively-driven algorithmic composition (AAC) is a rapidly growing field which exploits computer-aided composition in order to generate new music with particular emotional qualities or affective intentions. An AAC system was devised in order to generate a stimulus set covering 9 discrete sectors of a 2-dimensional emotion space by means of a 16 channel feed-forward artificial neural network. This system was used to generate a stimulus set of short pieces of music, which were rendered using a sampled piano t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…During the calibration and training sessions recordings of pre-generated music were used as stimuli. These were generated with the music generator described in 20 and are included with the datasets made available with this paper. During the testing session the synthetic music was generated in real-time and online (the synthetic generator used to generate the music clips is described in 20 ).…”
Section: Brain-computer Music Interface (Bcmi): Calibration Trainingmentioning
confidence: 99%
See 3 more Smart Citations
“…During the calibration and training sessions recordings of pre-generated music were used as stimuli. These were generated with the music generator described in 20 and are included with the datasets made available with this paper. During the testing session the synthetic music was generated in real-time and online (the synthetic generator used to generate the music clips is described in 20 ).…”
Section: Brain-computer Music Interface (Bcmi): Calibration Trainingmentioning
confidence: 99%
“…These were generated with the music generator described in 20 and are included with the datasets made available with this paper. During the testing session the synthetic music was generated in real-time and online (the synthetic generator used to generate the music clips is described in 20 ). Because these music stimuli was generated in real time during the experiment they differed between participants and are not included in our datasets.…”
Section: Brain-computer Music Interface (Bcmi): Calibration Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…For intelligent music system, scholars have carried out corresponding studies. Williams et al (2017), through designing the emotional-driven algorithm composition and applying 16-channel feedforward artificial neural network, found that the system could create short music sequences and effectively improve the emotional range in the stimulus set composed of real world and traditional music extracts [7]. Su et al (2017) proposed a new multimodal music recommendation system.…”
Section: Introductionmentioning
confidence: 99%